Intrusiveness and Scalability of OMPT-Based Tracing Tools for Task-based OpenMP Applications - Matos, Rayan Raddatz de; Schnorr, Lucas Mello (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2025: Anais do XXVI Simpósio em Sistemas Computacionais de Alto DesempenhoDO - 10.5753/sscad.2025.16751, 2025)
Task-based parallel programming has become popular for handling irregular parallelism in modern HPC applications. This paradigm requires tailored performance analysis tools, with the OpenMP Tools (OMPT) API being the state-of-the-art for tracing task-based execution events. However, since large-scale applications can generate enormous numbers of tasks, understanding the intrusion of OMPT callbacks and existing tracing tools is crucial. This article proposes a methodology to investigate and compare the intrusiveness and scalability of OMPT-based tracers, evaluating Score-P, Extrae, TiKKi, and custom tracers under various configurations that stress task numbers and registered events. We demonstrate that OMPT-based tracer intrusiveness varies significantly across tools, with some achieving low intrusion and good scalability while others exhibit substantial performance degradation as parallelism increases.